2018
DOI: 10.2196/10183
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Smartphone-Based Interventions to Empower Patients With Acute Coronary Syndromes: Qualitative Study on Health Care Providers’ Perspectives

Abstract: BackgroundPostdischarge interventions are limited in patients with acute coronary syndrome (ACS) due to few scheduled visits to outpatient clinics and travel from remote areas. Smartphones have become a viable lifestyle technology to deliver educational and health interventions following discharge from hospital.ObjectiveThe purpose of this study was to identify the requirements for the delivery of a mobile health intervention for the postdischarge management of patients with ACS via a multidisciplinary focus g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…The interview questions were adapted from previous studies in conducting qualitative studies on digital health technology design [ 39 , 40 ]. The interviews with pregnant women and postpartum women included questions related to their experience in monitoring their health and well-being during their pregnancy, in particular their previous and current use of digital health technology (activity trackers and health monitoring devices and apps), and their interest and intention to use technology to support the management of their pregnancy needs.…”
Section: Methodsmentioning
confidence: 99%
“…The interview questions were adapted from previous studies in conducting qualitative studies on digital health technology design [ 39 , 40 ]. The interviews with pregnant women and postpartum women included questions related to their experience in monitoring their health and well-being during their pregnancy, in particular their previous and current use of digital health technology (activity trackers and health monitoring devices and apps), and their interest and intention to use technology to support the management of their pregnancy needs.…”
Section: Methodsmentioning
confidence: 99%
“…Four major themes and their subthemes emerged from the qualitative analysis. The complete results of the focus group were published in 2018 [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…For ACS symptoms, clinicians recommended mainly focusing on educating patients instead of monitoring chest pain and shortness of breath daily, as these are subjective and may not sufficiently inform clinicians. Results of the focus group also suggested that monitoring health measures such as BP and BW may result in increased awareness of patient physical health, yet may not be sufficient to support patients with ACS via the smartphone-based intervention [ 24 ]. Therefore, monitoring pain, emotional status, and other health measures was recommended.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants identified the importance of real-time video conferencing. Old age and low education levels were identified as potential obstacles to the widespread use of smartphone-based systems [31].…”
Section: Smartphone-based Systemsmentioning
confidence: 99%